Sustainable Assessment in Improving English Proficiency - Sinaga, Reza Sanjaya; Sagala, Sepriyana; Silalahi, Dumaris E (Universitas Pahlawan Tuanku Tambusai, 2025)
Sustainable assessment plays a crucial role in enhancing student learning and improving English proficiency. However, the effectiveness of these practices in real-world classroom settings often remains under-explored. This study aims to investigate the perceptions and experiences of eighth-grade students regarding the implementation of sustainable assessment in English language learning at UPTD SMP Negeri 1 Pematangsiantar. A qualitative descriptive approach was employed, involving data collection through student questionnaires. The findings revealed varying levels of student satisfaction with the current assessment practices, with a preference for written tests and a desire for more diverse and engaging assessment methods. These findings highlight the importance of aligning assessment practices with diverse learning styles, providing timely and constructive feedback, and incorporating more authentic and engaging assessment tasks to optimize student learning and improve English proficiency.